Uganda’s pork value chain research and development outcomes: a status update - Ouma, Emily A.; Lukuyu, Ben A.; Kugonza, Donald, R.; Hasahya, Emmanuel; Mwema, Emmanuel; Achandi, Esther; Ahmed, Hardi; Namatovu, Jane; Marshall, Karen; Businge, Martha; Dione, Michel; Wairagala, Pamela; et al. (International Livestock Research Institute, 2024)
The CGIAR and its partners have invested in the pork value chain in Uganda since 2012 through research and development projects. By the end of the CGIAR Research Program in Livestock in 2021, there was increased knowledge, awareness and action in the pig sector. Several constraints affecting the pig value chains were identified and addressed by testing new innovations and best practices coupled with capacity development and enhancing actor collaborations as documented in Lukuyu and Ouma (2022). Nationally, pork was now recognized within the meat category prioritized in the Ministry of Agriculture, Animal Industries and Fisheries’ agro-industrialisation program (National Planning Authority, 2020). Pig population rose from 1.2 million in 1994 to 7.1 million in 2021 (Uganda Bureau of Statistics, 2024).